2003
DOI: 10.1063/1.1567803
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of enhanced light output efficiency in InGaN-based microlight emitting diodes

Abstract: Micro-light emitting diode ͑LED͒ arrays with diameters of 4 to 20 m have been fabricated and were found to be much more efficient light emitters compared to their broad-area counterparts, with up to five times enhancement in optical power densities. The possible mechanisms responsible for the improvement in performance were investigated. Strain relaxation in the microstructures as measured by Raman spectroscopy was not observed, arguing against theories of an increase in internal quantum efficiency due to a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 12 publications
5
80
0
Order By: Relevance
“…Our measurements also confirmed that the blue-shift in the blue QWs emission is too small to be observed due to the lower lattice mismatch between the active layers and barriers, which is consistent with our previous research. 4 Fig . 3 shows the simulated in-plane compressive strain distribution (i.e., the e xx , a component of the strain tensor) at the edge of a pillar with a diameter of 16 lm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our measurements also confirmed that the blue-shift in the blue QWs emission is too small to be observed due to the lower lattice mismatch between the active layers and barriers, which is consistent with our previous research. 4 Fig . 3 shows the simulated in-plane compressive strain distribution (i.e., the e xx , a component of the strain tensor) at the edge of a pillar with a diameter of 16 lm.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] The fabrication method has typically involved "top-down" patterning by etching an initially planar epitaxial structure containing InGaN/GaN QWs, although studies of directly grown nano-columnar structures have also been reported. 12 Correlations between spectroscopic results and numerical simulations of strain relaxation in the QWs were included in the reports by Yu et al 9 and Kawakami et al 10 The authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blue-shift has been attributed to several different factors, such as band renormalization and band filling [383], and the screening effect of the built-in [371]. Reproduced with permission piezoelectric field [384]. As shown in Fig.…”
Section: Inorganic Heterojunction Ledsmentioning
confidence: 99%
“…Additionally, periodic resonant modes can be observed in microdisk spectra, with a mode spacing of about 1.1nm, assigned to whispering gallery mode oscillations, as predicted by the relation ∆λ WG = λ 2 /2π Rn. 6 With increasing excitation power, non-linear increases-indicative of stimulated emission-are also observed in the intensities of the 365nm-peak beyond threshold conditions, as depicted in Figure 2(b). To conclude, a micro-cavity structure consisting of microdisks with undercuts fabricated on a GaN/Si substrate can enable optical confinement via whispering gallery modes.…”
mentioning
confidence: 83%